Can childcare work be designed to promote moderate and vigorous physical activity, cardiorespiratory fitness and health? Study protocol for the Goldilocks-childcare randomised controlled trial - Lidegaard, M.; Lerche, A.F.; Munch, P.K.; Schmidt, K.G.; Rasmussen, C.L.; Rasmussen, C.D.N.; Mathiassen, Svend; Straker, Leon; Holtermann, A. (2020)
Background: Despite extensive efforts, issues like obesity and poor physical capacity remain challenges for a healthy work life in several occupations. The Goldilocks work principle offers a new approach, encouraging design of productive work to promote physical capacity and health. This paper presents the protocol for the Goldilocks-childcare study, a randomised controlled intervention trial aiming to evaluate the effectiveness of implementing the Goldilocks work principle in childcare. The primary aim of the intervention is to increase time in moderate to vigorous physical activity (MVPA) by having the childcare workers act as active role models for children in daily playful physical activities, and thereby improve cardiorespiratory fitness and health of the workers.